E-cadherin expression in intestinal epithelium. Issue 2 (February 1995) - Doğan, A; Wang, Z D; Spencer, J
Abstract : AIMS--To investigate E-cadherin expression in normal and inflamed intestine, in the colonic adenocarcinoma cell line HT29, in normal fetal intestine, and in a fetal gut organ culture model where a T cell mediated enteropathy can be generated; to determine whether expression of E-cadherin changes in intestinal inflammation. METHODS--Immunohistochemistry was used to determine E-cadherin expression in following tissues: frozen and paraffin wax sections of normal and inflamed intestine; HT29 colonic adenocarcinoma cell line cultured on coverslips in the presence or absence of cytokines; frozen sections of fetal small intestinal tissue (gestational age 11-22 weeks); and frozen sections of cultured fetal gut in which a T cell mediated enteropathy had been induced. RESULTS--E-cadherin was strongly and evenly expressed by the epithelium in all specimens of intestine studied. Although there was no change in inflammation generally, in some cases of Crohn's disease groups of glands with the characteristic morphology of "ulcer associated cell lineage" showed lower expression of E-cadherin. In fetal gut organ cultures epithelial expression of E-cadherin was lower when local T cells were activated with mitogens, compared with control explants. By contrast, the HT29 cell line showed low levels of expression which increased after treatment with conditioned medium from activated tonsil cells. CONCLUSIONS--E-cadherin is strongly and evenly expressed by epithelium in normal and inflamed intestine, although an increase in E-cadherin expression in cytokine treated HT29 cells was observed. E-cadherin expression is reduced in the epithelium adjacent to ulcers (ulcer associated cell lineage), possibly to assist regeneration.